OSTEOCONDROMA MONOSTÓSICO UMERAL EM CÃO: RELATO DE CASO - Perez, Gabriel Victor Werlang Gomez; Garcia, Felipe; Schneider, Marla; Massa, Isadora Morais; Carneiro, Maico Fernando Wilges; Pinheiro, Fernanda (Anais de Medicina Veterinária, 2022)
.